2019
DOI: 10.1093/jas/skz092
|View full text |Cite
|
Sign up to set email alerts
|

ASN-ASAS SYMPOSIUM: FUTURE OF DATA ANALYTICS IN NUTRITION: Mathematical modeling in ruminant nutrition: approaches and paradigms, extant models, and thoughts for upcoming predictive analytics1,2

Abstract: This paper outlines typical terminology for modeling and highlights key historical and forthcoming aspects of mathematical modeling. Mathematical models ( MM ) are mental conceptualizations, enclosed in a virtual domain, whose purpose is to translate real-life situations into mathematical formulations to describe existing patterns or forecast future behaviors in real-life situations. The appropriateness of the virtual representation of real-life situations through MM depends on the model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 190 publications
2
53
0
5
Order By: Relevance
“…As suggested above, reaching valuable global markets increasingly require quality products supported by documented, low carbon foot printing (McAulifee et al 2018). This is consistent with Godde et al (2019) and Tedeschi et al (2002Tedeschi et al ( , 2019, who argued that in the face of climate variability it is critical to use modelling approaches to capture short and long, simple and complex environmental livestock representations of earlier or current real-life farming systems in tropical Australian rangelands or elsewhere. Therefore, baseline data and scenarios for various environmental burdens from savanna-beef based production systems in Colombia are desirable to integrate local deep knowledge-sharing and data-driven modelling.…”
Section: Introductionsupporting
confidence: 55%
“…As suggested above, reaching valuable global markets increasingly require quality products supported by documented, low carbon foot printing (McAulifee et al 2018). This is consistent with Godde et al (2019) and Tedeschi et al (2002Tedeschi et al ( , 2019, who argued that in the face of climate variability it is critical to use modelling approaches to capture short and long, simple and complex environmental livestock representations of earlier or current real-life farming systems in tropical Australian rangelands or elsewhere. Therefore, baseline data and scenarios for various environmental burdens from savanna-beef based production systems in Colombia are desirable to integrate local deep knowledge-sharing and data-driven modelling.…”
Section: Introductionsupporting
confidence: 55%
“…Our simulation suggests that AI methods have not been designed for precision, but accuracy, and requires larger dataset to perform adequately as well as the human element for judgment (i.e., knowledge and wisdom; Tedeschi, 2019). It seems that ML can accurately predict methane emission, but lacks precision compared to MLR.…”
Section: Discussionmentioning
confidence: 94%
“…Since then, substantial progress in mathematical modeling has been absent, almost reaching to a halt. Artificial intelligence (AI) might incentivize an avant-garde technological wave in predictive analytics (Tedeschi, 2019), but the scientific community has a long way to go. The objective of this study was to compare AI methods with least-squares regression to predict methane emission.…”
Section: Resultsmentioning
confidence: 99%
“…Some have suggested that such problems are rooted in communication and training as opposed to user-friendliness (Cartwright et al, 2016), and protocols to improve the user experience, such as customer journey mapping, are recommended (Vasilieva, 2018). Tedeschi (2019) reflected that innovation in MM for ruminant nutrition had gone stagnant since 2010 and proposed several reasons why, including (1) the field had reached a certain level of maturity or that (2) students are not being properly introduced to the required 'systems thinking' approach. We further suggest that the 'lag' observed by Tedeschi (2019) could have an additional origin related to reaching a level of success with nutritional models beyond which we need to integrate with other disciplinesgenetics, epigenetics, health, animal management, environment, whole farm modelling and life cycle assessmentbefore further knowledge (and then wisdom) can be extracted from the generated models.…”
Section: Approach Limitations: Mechanistic Modelsmentioning
confidence: 99%
“…The use of models in animal agriculture Models of all types (Figure 1) have a strong history of application in animal production, where their objectives have typically revolved around optimally feeding and growing livestock. For an excellent review of the historical evolution of model development and use, for example, in ruminant nutrition, see Tedeschi (2019). Such a development path has largely been paralleled in swine and poultry (Dumas et al, 2008;Sakomura et al, 2015).…”
Section: Introductionmentioning
confidence: 99%